Rheologic Behavior of Bovine Calf Serum - Wonerow, Tanja; Uhler, Maximilian; Nuppnau, Jens; Kretzer, Jan Philippe; Mantwill, Frank (Materials, 2021)
Recent studies have illuminated the rheological behavior of synovial fluid and the role of protein and hyaluronan (HA). However, with respect to artificial joint replacement in standardized wear simulations, bovine serum is used as fluid test medium. Little is known about the rheological characteristics of bovine serum, which are needed for precise tribological investigations. The steady shear viscosity η of bovine calf serum is determined for protein concentrations used in standardized wear simulations depending on shear rate γ˙ and temperature T. Additionally, the density of the serum is determined for both protein concentrations. The results show shear thinning behavior of bovine calf serum with a nearly Newtonian behavior in the range of high shear rates. Within the range of high shear rates, mean viscosities of η = 0.82-0.88 mPa·s were found for protein concentrations of 20 g/L and mean viscosities of η = 0.88-0.94 mPa·s for 30 g/L, decreasing with temperature. Densities of 1.004-1.005 g/cm3 and 1.007-1.008 g/cm3 were found for 20 and 30 g/L protein concentrations, respectively.
Gesehen am 03.09.2021